Budaya Populer Dalam Perspektif Komunikasi Lintas Budaya - Nurul Khotimah (IQTIDA : Journal of Da'wah and Communication, 2021)
Popular culture is a commodity in the industrial world. Teenagers, as parties who have a high dynamic level, are open to change and new things and are easy to influence, the 'land' for the industrial world to make them targets in spreading the concept of popular culture with the existing role of new media. One of these phenomena is how crosscultural communication is seen from the point of view of popular culture that is currently happening. Basically every human behavior and activity is communication. both verbal and non-verbal communication containing intercultural or cross-cultural dimensions. If we agree with this assumption, then it has become an obligation for every individual to study and recognize every cultural behavior of individuals and groups. The development of the times is so fast, accompanied by the current of modernization that is increasingly unstoppable. As well as changes in the lifestyle of most people, from a traditional lifestyle to a metropolitan lifestyle, all aspects of life participate in the current of modernization. This is one of the factors of the emergence of popular culture.